Los sindicatos y las juntas de acción comunal en Colombia - Londoño Botero, Rocío (América Latina Hoy, 2009)
RESUMEN: El artículo examina el estado en que se encuentran las organizaciones populares y, en general, los actores sociales en Colombia y sus respuestas a la transformación del régimen político después de la Constitución de 1991, a la apertura económica, a la reducción del Estado y a la violencia política. Después de una breve retrospectiva, la autora se centra en los sindicatos y las experiencias de acción comunal, para ensayar finalmente una visión de futuro. ABSTRACT: The article analyses the situation of popular organizations as well as the situation for the rest of Colombian social actors. It also focuses on answers of: the political transformation of the regime after the Constitution of 1991, the economical opening process, the state reduction and to the political violence. After a brief retrospective, the author focuses the atention on the study of trade unions and comunitarian action experiences. And finally she gives us a kind of future perspective about all these questions.